Rapid encapsulation of true ferns and arborane/fernane compounds fossilised in siderite concretions supports analytical distinction of plant fossils - Tripp, Madison; Schwark, Lorenz; Brocks, J.J.; Mayer, P.; Whiteside, J.H.; Rickard, William; Greenwood, Paul; Grice, Kliti (2023)
Fossilised true ferns (Pecopteris sp.) preserved in siderite concretions from the Mazon Creek Lagerstätte (Illinois) presented a unique opportunity to characterise the organic signatures of these late Carboniferous plants. Localised analyses of true fern fossils showed several highly abundant phytohopanoids and fernane/arborane derived aromatic products, which were present only negligibly within their siderite matrix, as well as from other types of fossilised plants. These terpenoids had been recognised in some extant ferns, but scarcely in sedimentary organic matter and their exact source remained ambiguous. The present fossil biomarker data confirms an ancient true fern origin. Furthermore, the excellent concretion preservation of a series of related terpenoid products provided a rare insight into their diagenetic formation. The benign properties of carbonate concretions could be exploited further for biomarker evidence of other fossilised organisms, with one important caveat being that biomarker signals attributed to isolated fossils be significantly distinct from background organic matter pervading the concretion matrix. For instance, hydrocarbon profiles of seed ferns (pteridosperms) and articulates (horsetails) also preserved in Mazon Creek concretions were indistinguishable from separate analysis of their concretion matrix, preventing biomarker recognition.